Terminal Barang Internasional (TBI) dalam Konteks Pembangunan Ekonomi Masyarakat di Perbatasan Entikong, Indonesia-Malaysia - Nikodemus Niko; Samkamaria Samkamaria (Indonesian Journal of Religion and Society, 2019)
Entikong has the potential for economic growth, strategic location, and formal access support that is already capable and advanced. This article explores the impact of the construction of an international terminal goods (Terminal Barang Internasional) at the border of Entikong on the economic development potential of border communities. The method used is a descriptive exploratory where the data sources derived from primary data (interviews and opinion actors), while secondary data from the review desk results related to the economic development of the community in the country's border area. With the accessible of Entikong's border to Malaysia makes economic growth in the region is a good implication towards improving the welfare of local communities. Especially with the construction of international Terminal (TBI) at the border of Entikong, it is hoped that Entikong is able to grow rapidly and make this frontier region as a growth motor for the government of Sanggau Regency in particular and West Kalimantan in general.